Species-specific tropism determinants in the human immunodeficiency virus type 1 capsid - Hatziioannou, Theodora; Cowan, Simone; Von Schwedler, Uta K; Sundquist, Wesley I; Bieniasz, Paul D (Journal of virology, 2004)
Retroviral tropism is determined in part by cellular restriction factors that block infection by targeting the incoming viral capsid. Indeed, human immunodeficiency virus type 1 (HIV-1) infection of many nonhuman primate cells is inhibited by one such factor, termed Lv1. In contrast, a restriction factor in humans, termed Ref1, does not inhibit HIV-1 infection unless nonnatural mutations are introduced into the HIV-1 capsid protein (CA). Here, we examined the infectivity of a panel of mutant HIV-1 strains carrying substitutions in the N-terminal CA domain in cells that exhibit restriction attributable to Lv1 or Ref1. Manipulation of HIV-1 CA could alter HIV-1 tropism, and several mutations were identified that increased or decreased HIV-1 infectivity in a target-cell-specific manner. Many residues that affected HIV-1 tropism were located in the three variable loops that lie on the outer surface of the modeled HIV-1 conical capsid. Some tropism determinants, including the CypA binding site, coincided with residues whose mutation conferred on HIV-1 CA the ability to saturate Ref1 in human cells. Notably, a mutation that reverses the infectivity defect in human cells induced by CypA binding site mutation inhibits recognition by Ref1. Overall, these findings demonstrate that exposed variable loops in CA and a partial CypA "coat" can modulate restriction and HIV-1 tropism and suggest a model in which the exposed surface of the incoming retroviral capsid is the target for inhibition by host cell-specific restriction factors.